The Effect of Talent Management, Work Motivation, and Training on Employee Productivity in Service Organizations - Eko Cahyo Mayndarto; Ita Soegiarto (Malaqbi Publisher, 2026)
Employee productivity is a critical determinant of organizational success in service-based industries, where performance outcomes are highly dependent on human capital effectiveness. This study aims to examine the effect of talent management, work motivation, and training on employee productivity in service organizations. A quantitative explanatory research design was employed, and data were collected from 200 employees working in various service sectors using a structured questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The results indicate that talent management, work motivation, and training each have a significant positive effect on employee productivity, with training demonstrating the strongest influence. The model explains a substantial proportion of variance in employee productivity, highlighting the importance of integrated human resource management practices. These findings suggest that service organizations should prioritize strategic talent management, enhance employee motivation, and invest in continuous training programs to improve productivity and sustain competitive advantage. This study contributes to the human resource management literature by providing empirical evidence on the combined influence of strategic and psychological factors on employee productivity in service contexts.